Antimicrobial peptides in human corneal tissue of patients with fungal keratitis. Issue 8 (27th August 2020) - Mohammed, Imran; Mohanty, Debasmita; Said, Dalia G.; Barik, Manas Ranjan; Reddy, Mamatha M; Alsaadi, Ahmed; Das, Sujata; Dua, Harminder Singh; Mittal, Ruchi
Abstract : Background: Fungal keratitis (FK) is the leading cause of unilateral blindness in the developing world. Antimicrobial peptides (AMPs) have been shown to play an important role on human ocular surface (OS) during bacterial, viral and protozoan infections. In this study, our aim was to profile a spectrum of AMPs in corneal tissue from patients with FK during the active pase of infection and after healing. Methods: OS samples were collected from patients at presentation by impression cytology and scraping. Corneal button specimens were collected from patients undergoing therapeutic penetrating keratoplasty for management of severe FK or healed keratitis. Gene expression of human beta-defensin (HBD)-1, -2, -3 and -9, S100A7, and LL-37 was determined by quantitative real-time PCR. Results: Messenger RNA expression (mRNA) for all AMPs was shown to be significantly upregulated in FK samples. The levels of HBD-1 and -2 mRNA were found to be elevated in 18/20 FK samples. Whereas mRNA for HBD-3 and S100A7 was upregulated in 11/20 and HBD9 was increased in 15/20 FK samples. LL-37 mRNA showed moderate upregulation in 7/20 FK samples compared with controls. In healed scar samples, mRNA of all AMPs was found to be low and matching the levels in controls. Conclusion: AMP expression is a consistent feature of FK, but not all AMPs are equally expressed. HBD-1 and -2 are most consistently expressed and LL-37 the least, suggesting some specificity of AMP expression related to FK. These results will help to identify HBD sequence templates for designing FK-specific peptides to test for therapeutic potential.